Total staff costs to implement a decision support system in nursing - Valéria Castilho; Antônio Fernandes Costa Lima; Fernanda Maria Togeiro Fugulin; Heloisa Helena Ciqueto Peres; Raquel Rapone Gaidzinski (Universidade de São Paulo, 2014)
OBJECTIVE: to identify the direct labor (DL) costs to put in practice a decision support system (DSS) in nursing at the University Hospital of the University of São Paulo (HU-USP). METHOD: the development of the DSS was mapped in four sub-processes: Conception, Elaboration, Construction and Transition. To calculate the DL, the baseline salary per professional category was added to the five-year additional remuneration, representation fees and social charges, and then divided by the number of hours contracted, resulting in the hour wage/professional, which was multiplied by the time spend on each activity in the sub-processes. RESULTS: the DL cost corresponded to R$ 752,618.56 (100%), R$ 26,000.00 (3.45%) of which were funded by a funding agency, while R$ 726,618.56 (96,55%) came from Hospital and University resources. CONCLUSION: considering the total DL cost, 72.1% related to staff wages for the informatics consulting company and 27.9% to the DL of professionals at the HU and the School of Nursing.